RUANG AJAR BALANG: FASILITAS EDUKASI PEMANFAATAN DAN PENGOLAHAN ECENG GONDOK DI SUNGAI SIAK - Vellisa Chou; Djidjin Wipranata (Jurusan Arsitektur dan Perencanaan, 2021)
According to data from the Data and Information Center of the Ministry of Agriculture (Kementan 2019), Riau Province is the largest palm oil producer in Indonesia with an area of 2,430.51 ha and an average production of 8,605.65 thousand tons annually. However, the high activity of the palm oil industry causes damage to the ecosystem around the river due to waste disposal which causes high metal contentin the water and siltation in the Siak River. Therefore, it is necessary to carry out handling in the form of wastewater treatment with natural biofiltration, one of which is water hyacinth. In addition to being economical, this aquatic plant has the potential to grow quickly. Balang-balang Learning Area is an educational center for water hyacinth as a heavy metal purification in the Siak River, Riau. In this project, utilize the potential of water hyacinth as a natural biofiltration that can purify heavy metals in the water content of the Siak River until 99.70% (Rosida, 2018). The growth of water hyacinth has become a potential for handicraft businesses and space installations. Therefore, the growth of water hyacinth can be controlled so that it does not interfere with wastewater treatment activities. In designing this project using a combination of locality and contextual design methods, it is hoped that the project can have elements of harmony and balance with localities in Siak Regency. The presence of the Balang-balang Learning Area is expected to be a facility that can educate the public on the potential of water hyacinth as a heavy metal purifier and its economic benefits. Keywords: education; purification; water hyacinth. AbstrakBerdasarkan data yang dilansir dari Pusat Data dan Informasi Kementerian Pertanian (Kementan 2019), Provinsi Riau merupakan penghasil kelapa sawit terbesar di Indonesia dengan luas mencapai 2.430,51 ha dan produksi mencapai rata-rata 8.605,65 ribu ton setiap tahunnya. Namun, tingginya aktivitas industri sawit menyebabkan rusaknya ekosistem yang berada di sekitar sungai akibat pembuangan limbah yang menyebabkan tingginya kandungan logam pada air dan pendangkalan di Sungai Siak. Maka dari itu perlu dilakukan penanggangan berupa pengolahan air limbah dengan biofiltasi alami, salah satunya adalah dengan eceng gondok. Selain ekonomis, tumbuhan air ini memiliki potensi perkembangan yang sangat cepat. Ruang Ajar Balang-balang merupakan pusat edukasi eceng gondok sebagai purifikasi logam berat di Sungai Siak, Riau. Proyek ini, memanfaatkan potensi eceng gondok sebagai biofiltrasi alami yang dapat mempurifikasi logam berat pada kandungan air di Sungai Siak sebesar 99,70% (Rosida, 2018). Perkembangan eceng gondok yang pesat menjadi potensi bagi usaha kerajinan tangan dan instalasi ruang. Dengan demikian perkembangan eceng gondok dapat dikendalikan sehingga tidak mengganggu aktivitas pengolahan air limbah. Pada perancangan proyek ini menggunakan penggabungan metode perancangan lokalitas dan kontekstual diharapkan proyek dapat memiliki unsur serasi dan seimbang terhadap lokalitas di Kabupaten Siak. Hadirnya Ruang Ajar Balang-balang diharapkan menjadi fasilitas yang dapat mengedukasi masyarakat terhadap potensi eceng gondok sebagai purifikasi logam berat dan manfaat ekonomi yang dimilikinya.